Wireless Sensor Networks : 12th European Conference, EWSN 2015, Porto, Portugal, February 9-11, 2015. Proceedings - Abdelzaher, Tarek; Pereira, Nuno.; Tovar, Eduardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 12 European Conference on Wireless Sensor Networks, EWSN 2015, held in Porto, Portugal, in February 2015. The 14 full papers and 9 short papers presented were carefully reviewed and selected from 85 submissions. They cover a wide range of topics grouped into five sessions: services and applications, mobility and delay-tolerance, routing and data dissemination, and human-centric sensing.
Services and applications -- Mobility and delay-tolerance -- Routing and data dissemination -- Human-centric sensing.
Keywords: Computer Communication Networks; Software engineering; Computer system performance; Computer software; Computer Communication Networks; Special Purpose and Application-Based Systems; System Performance and Evaluation; Algorithm Analysis and Problem Complexity; Software Engineering; Information Systems Applications (incl. Internet).